2017
DOI: 10.1111/mpp.12631
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the β‐glucosidase BglC to the onset of the pathogenic lifestyle of Streptomyces scabies

Abstract: 2Common scab disease on root and tuber plants is caused by Streptomyces scabies and related 2 3 species which use the cellulose synthase inhibitor thaxtomin A as main phytotoxin. 4Thaxtomin production is primarily triggered by the import of cello-oligosaccharides. Once 2 5 inside the cell, the fate of the cello-oligosaccharides is dichotomized into i) fueling glycolysis 2 6with glucose for the saprophytic lifestyle through the action of β -glucosidase(s) (BG), and ii) reduced production of thaxtomin when the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…The role of CWDEs in the virulence of plant pathogens has been described by previous studies, while these enzymes are considered vital for the generation of disease symptoms and pathogenesis (Brito et al, 2006;Kubicek et al, 2014;Pérez-Hernández et al, 2017;Gui et al, 2018). The β-glucosidases are among the main CWDEs, and thus play important roles especially in the virulence of necrotrophic pathogens infection and disease development (Sasaki and Nagayama, 1996;Pérez-Hernández et al, 2017;Jourdan et al, 2018). V. mali, the causal agent of apple tree Valsa canker, infects host plants and causes typical symptoms through secreted CWDEs and toxins.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The role of CWDEs in the virulence of plant pathogens has been described by previous studies, while these enzymes are considered vital for the generation of disease symptoms and pathogenesis (Brito et al, 2006;Kubicek et al, 2014;Pérez-Hernández et al, 2017;Gui et al, 2018). The β-glucosidases are among the main CWDEs, and thus play important roles especially in the virulence of necrotrophic pathogens infection and disease development (Sasaki and Nagayama, 1996;Pérez-Hernández et al, 2017;Jourdan et al, 2018). V. mali, the causal agent of apple tree Valsa canker, infects host plants and causes typical symptoms through secreted CWDEs and toxins.…”
Section: Discussionmentioning
confidence: 96%
“…Thaxtomin is the main phytotoxin produced by S. scabies. However, the underlying mechanism of BglC in the virulence of S. scabies is more complex than commonly perceived (Jourdan et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the past decades, a set of in vivo genome editing methods have been developed to facilitate pathway engineering and modification. However, previous studies for genome editing in Streptomyces were mainly based on the traditional double crossover or single crossover . Luckily, with the advent of CRISPR systems, tools for site‐specific genome editing in Streptomyces were rapidly developed (Figure ).…”
Section: Current Synthetic Biology Tools Developed For Applications Imentioning
confidence: 99%
“…Previous work demonstrated that cebR is the cellobiose‐sensing key, which locks the expression of txtR , while txtR is the key necessary to unlock the production of phytotoxin . With the understanding of the regulation relationship between the regulons cebR and txtR , the constitutive thaxtomin A production and hypervirulence of Streptomyces scabies were obtained by the cebR deletion . In addition, the increase of milbemycin production was attributed to the deletion of SbbA in the SbbR/SbbA pair (an important ArpA/AfsA ‐like system) in a BGC from Streptomyces bingchenggensis BC04 .…”
Section: Pathway‐specific Engineering To Exploit Natural Products Biomentioning
confidence: 99%